2022
DOI: 10.3389/fonc.2022.932689
|View full text |Cite
|
Sign up to set email alerts
|

GPR12 Inhibits Apoptosis in Epithelial Ovarian Cancer via the Activation of ERK1/2 Signaling

Abstract: Epithelial ovarian cancer (EOC) is one of the most lethal gynecological malignancies in women worldwide. G protein–coupled receptor 12 (GPR12) is a member of G protein–coupled receptors (GPCRs) and plays an important role in the regulation of cell proliferation and survival. However, its role in EOC is underappreciated. In this study, we found that GPR12 is highly expressed in the EOC tissues and can be an ideal biomarker to predict the prognosis of patients with EOC. GPR12 knockdown obviously inhibits the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Overactivation of ERK1/2 signaling enhances cell proliferation and promotes malignant transformation [ 34 ]. Indeed, research has shown that activation of the ERK1/2 pathway contributes to ovarian tumor growth [ 32 , 59 , 60 ]. In our study, the expression of phosphorylated ERK1/2 was significantly reduced after ANGPTL4 knockdown or ERK1/2 inhibition with PD98059.…”
Section: Discussionmentioning
confidence: 99%
“…Overactivation of ERK1/2 signaling enhances cell proliferation and promotes malignant transformation [ 34 ]. Indeed, research has shown that activation of the ERK1/2 pathway contributes to ovarian tumor growth [ 32 , 59 , 60 ]. In our study, the expression of phosphorylated ERK1/2 was significantly reduced after ANGPTL4 knockdown or ERK1/2 inhibition with PD98059.…”
Section: Discussionmentioning
confidence: 99%